(untitled) (Revista de Ciências Agroveterinárias, 2015)
Toona ciliata M. Roem. belongs to the Meliaceae bothanic family introduced in Brazil because this species has excellent technological characteristics for the sawmill. However, despite being in the country for many decades, studies related to the seedlings production are rare. The objective of this study was to evaluate the effect of two samples of marketed T. ciliata seeds and evaluate the initial development of seedlings on different substrates. Two samples of different locations were used, Santa Catarina and Bahia, and six substrates, constituting the treatments: T1 - commercial substrate Carolina Soil®; T2 - commercial substrate Beifort®; T3 - coconut fiber; T4 - vermiculite; T5 - in nature rice husk and; T6 - carbonized rice husk. For each treatment, 200 seeds were divided into eight replicates, which were distributed in plastic boxes. The design was a completely randomized factorial with 2 x 6 (samples x substrates), totaling twelve treatments. The variables evaluated were: Emergence at 20 and 40 days (E20 and E40), Emergence Velocity Index (EVI), full length (FL), root length (RL), shoot length (SL), number of true leaves (NTL), and seedling dry weight (DW). There was a difference between seeds samples, where sample from Bahia had higher values. Regard the substrates, the best were vermiculite and carbonized rice husk which provided greater EVI, E20 and E40, FL, DW and NTL.